2019
DOI: 10.1108/ijph-11-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of HBV in HIV-infected prisoners in Mozambique

Abstract: Purpose The purpose of this paper is to determine the prevalence of hepatitis B virus (HBV) among 448 HIV-infected prisoners from 32 prisons in Mozambique. Design/methodology/approach All HIV seropositive prisoners were screened for HBV. Findings Of the 448 HIV seropositive prisoners, 51 (11.4 percent, 95%CI: 9.3–13.9 percent) were HBsAg-positive and was significantly higher in prisoners aged<25 years. Originality/value Data from this study show for the first time that the frequency of HBV among HIV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Population-based studies conducted in Mozambique have reported HBV infection rates of 11.4% in prisoners [ 15 ], 13.2% in refugees [ 16 ], 4.5% to 9.3% in blood donors [ 17 , 18 ], 5.9% to 32.8% in persons who use drugs [ 19 ], 12.2% in young adults [ 13 ], 7.6% in HIV-positive adults initiating antiretroviral therapy [ 20 ], and 4.0% in pregnant women [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies conducted in Mozambique have reported HBV infection rates of 11.4% in prisoners [ 15 ], 13.2% in refugees [ 16 ], 4.5% to 9.3% in blood donors [ 17 , 18 ], 5.9% to 32.8% in persons who use drugs [ 19 ], 12.2% in young adults [ 13 ], 7.6% in HIV-positive adults initiating antiretroviral therapy [ 20 ], and 4.0% in pregnant women [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other Southern African countries, Mozambique is considered endemic for HBV [ 13 , 14 ]. Population-based studies conducted in Mozambique have reported HBV infection rates of 11.4% in prisoners [ 15 ], 13.2% in refugees [ 16 ], 4.5% to 9.3% in blood donors [ 17 , 18 ], 5.9% to 32.8% in persons who use drugs [ 19 ], 12.2% in young adults [ 13 ], 7.6% in HIV-positive adults initiating antiretroviral therapy [ 20 ], and 4.0% in pregnant women [ 21 ]. Most studies of HBV in Mozambique have been conducted in the capital city of Maputo, and information regarding viral diversity in the other regions of the country is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported the prevalence of HBV/HIV as 15% in Africa [ 64 ]. However, there is limited data on the HBV/HIV co-infection in the African region, as only about 2% of prisoners are tested for HBV (before or during incarceration) in the region [ 83 ]. Also, only 14% of African prisoners have heard about hepatitis before being incarcerated, and HBV screening or vaccination is not a routine procedure in the prisons of this region [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although limited data is available on the frequency and dynamics of risky sexual activities in detention centers and jails, it is suggested that, in the absence of access to condom and lubricants, sex for pleasure or in exchange for drug, money, personal protection, food, or other goods is common in prisons and this risky behavior is even more common among prisoners with HIV [ 3 , 83 ].…”
Section: Discussionmentioning
confidence: 99%